2015
DOI: 10.2337/dc15-0563
|View full text |Cite
|
Sign up to set email alerts
|

Use of an α-Glucosidase Inhibitor and the Risk of Colorectal Cancer in Patients With Diabetes: A Nationwide, Population-Based Cohort Study

Abstract: OBJECTIVEAcarbose, an a-glucosidase inhibitor, has been shown to have antineoplastic effects on colorectal cancer in biomarker studies. We assessed the association between acarbose use in patients with diabetes and incident colorectal cancer. RESEARCH DESIGN AND METHODSWe conducted a nationwide, population-based study using a large cohort with diabetes in the Taiwan National Health Insurance Research Database. Patients with newly diagnosed diabetes (n = 1,343,484) were enrolled between 1998 and 2010. One contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 35 publications
(30 reference statements)
1
30
0
3
Order By: Relevance
“…We found that ACA improved median survival of Apc +/Min mice by 21.4% (Figure b, p = .0002) and that the longest‐lived mouse showed a 149% increase in lifespan compared to control. Our findings are in accord with the observation that diabetic patients receiving ACA display less colon cancer (Tseng, Tsan, Chan, Sheu, & Chen, ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We found that ACA improved median survival of Apc +/Min mice by 21.4% (Figure b, p = .0002) and that the longest‐lived mouse showed a 149% increase in lifespan compared to control. Our findings are in accord with the observation that diabetic patients receiving ACA display less colon cancer (Tseng, Tsan, Chan, Sheu, & Chen, ).…”
Section: Resultssupporting
confidence: 92%
“…Hence, a high dose of ACA could be used to suppress polyposis and tumorigenesis. Furthermore, ACA given to diabetic patients showed less colon cancer supporting the use of ACA in treating people with FAP (Tseng et al, ). ACA is well‐tolerated in patients (Hanefeld & Schaper, ) and rapamycin has a black box describing it as an immunosuppressant.…”
Section: Discussionmentioning
confidence: 97%
“…A cohort of 275, 164 T2DM patients found no evidence for altered cancer risk for repaglinide or α-glucosidase inhibitors compared to insulin-based therapies or other oral glucose-lowering drugs [216]. In other reports, acarbose was associated with reduced the risk of incident CRC in patients with diabetes in a dose-dependent manner [238, 239]. Acarbose may alter the microbiota [240] and decreased the size of gastrointestinal adenomas in Apc knockout mice [241].…”
Section: Implications For Therapymentioning
confidence: 99%
“…Patients with incident diabetes were further selected by excluding patients diagnosed with diabetes prior to January 1, 1998. 20 Based on data availability, the current study included patients with diabetes between January 1, 2000 and December 31, 2010 for analysis. The study was approved by the National Taiwan University Hospital Research Ethics Committee.…”
Section: The National Health Research Institute Created the Taiwan Namentioning
confidence: 99%